Tratamento de semente de milho com suspensão concentrada à base de zinco - Bonotto, Ivan (2008)
The perspective for maize are very encouraging, in view of the global needs for food, feed, and more recently, for clean energy. The Brazil is the third in this cereal production among the U.S.A and China and has high potential for growth in production, with the following advantages, such as production area, available water, potential to produce two annual crops, research institutes, etc. However, it is estimated that about 170 million ha of soils under savannah vegetation (brazilian cerrado) of Midwest of Brazil, are deficient in zinc. According to studies for various crops, including maize, there is the large number of information about applications micronutrient by foliar, soil, and seed treatment, using various sources such as salts, oxides, etc, with positive results in yields. Thus the present work aims to study the behavior of maize to zinc which was applied in seed treatment, with suspension concentrated product based on zinc oxide. The experiment was conducted in a greenhouse at the Federal University of Uberlandia (MG). The experimental design was randomized, and doses of zinc in the seed treatment were based on exports of zinc by corn, according to the average value of 27.6 g Zn per 1000 kg of grain with the expectation from the yield of 9.0 t ha-1 in grains, being equivalent to 248.40 g ha-1 Zn. For the comparison to the seed treatment with zinc was used the Hoagland solution which has a soluble source of zinc as sulfate. According to results from the material collected 30 days after emergence, it was observed that for zinc contained in the dry mass of total plant, the seed treatment with fertilizer concentrated suspension obtained the best performance and did not differ statistically from treatment with complete Hoagland solution, which provided zinc as sulphate. Thus, according to the regression curve the best dosage of seed treatment with zinc was 173,45% of exports of the nutrient to an expected yield of 9,0 t ha-1, corresponding to 430 g of zinc for a total of 88,888 seeds.